2012
DOI: 10.1055/s-0032-1311991
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Identification of Lupus Anticoagulants

Abstract: The main laboratory characteristic of lupus anticoagulants (LA) is their ability to prolong phospholipid-dependent clotting time in vitro. The laboratory demonstration of LA requires a systematic approach combined with an awareness of the many variables that can affect test results. The ideal testing procedures are those sensitive enough to detect weak LA and specific enough so as not to produce incorrect conclusions. International guidelines have been published to assist laboratories in applying correct testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 19 publications
1
59
0
Order By: Relevance
“…and Kershaw et al. investigated LA sensitivity of commercial APTT reagents such as Pathromtin SL, Synthasil IL, APTT LT, and KPTT in addition to the PTT, FSL, and SP used in this study 40, 41. Their results showed that the LA sensitivity of ellagic acid‐activated FSL was lower than that of PTT and SP, silica‐based reagents.…”
Section: Discussionmentioning
confidence: 89%
“…and Kershaw et al. investigated LA sensitivity of commercial APTT reagents such as Pathromtin SL, Synthasil IL, APTT LT, and KPTT in addition to the PTT, FSL, and SP used in this study 40, 41. Their results showed that the LA sensitivity of ellagic acid‐activated FSL was lower than that of PTT and SP, silica‐based reagents.…”
Section: Discussionmentioning
confidence: 89%
“…Current LA guidelines [5] suggest that laboratories use ' at least 40 adult healthy donors ' and take ' the cut-off as the value above the 99th percentile of the distribution ' . This has caused some contention in the field, given that a statistically valid 99th percentile evaluation of a nonGaussian distributed normal population would require a minimum of nearly 400 samples [6] . Pradella and colleagues [1] comparatively evaluated the data obtained in each assay, as well as assay ratios, in each center, as well as the composite of all study data.…”
Section: This Issue Of Clinical Chemistry and Laboratory Medicinementioning
confidence: 99%
“…Thrombin generation assays [23,24] along with thromboelastography [25,26] are additional useful " global " tests of hemostasis, which have not found, however, widespread application in clinical and laboratory practice. Second line assays are typically those designed to provide further insights into abnormalities of screening tests, or used to monitor more accurately some antithrombotic therapies, and thereby include clotting factors assays [27] , ristocetin-induced platelet agglutination and VWF antigen tests [28] , anticardiolipin (aCL) IgG and IgM, anti-β (2) glycoprotein I (anti-β (2) GPI) antibodies IgG and IgM and phospholipid-dependent coagulation assays [29,30] , platelet function tests such as Platelet Function Analyzer-100 (PFA-100) and aggregometry [31,32] , assays for heparin-induced thrombocytopenia [33,34] , additional tests for thrombophilia screening including resistance to activated protein C, antithrombin, proteins C and S, and genetic polymorphisms/mutations (e.g., prothrombin G20210A and factor V Leiden) [35,36] along with ecarin clotting time, chromogenic anti-factor Xa and dilute Russell viper venom time (dRVVT) for monitoring novel anticoagulants [37,38] . Both first and second line tests might be available to most clinical laboratories, whereas third line tests -which are intended to troubleshoot the most challenging conditions and encompass analyses such as VWF collagen binding, VWF ristocetin cofactor assay, VWF-FVIII binding assay, multimer and molecular analysis for the precise classification of VWD [39,40] , coagulation factors inhibitors testing [41,42] , analyses of rare thrombophilic mutations [43] , rare platelet functional disorders [44] , pharmacogenetics testing [45,46] -are occasionally used and typically available in specialized laboratories.…”
Section: Laboratory Hemostasismentioning
confidence: 99%